STUDI MAKANAN IKAN LUNDU (Arius maculatus Thunberg, 1792) DI PANTAI MAYANGAN, JAWA BARAT [Study on Food of Catfish, Arius maculatus Thunberg, 1792 in Mayangan Coastal, West Java] - Djadja S. Sjafei; Ridwan Affandi; Rika Fauziah (Jurnal Iktiologi Indonesia, 2004)
The research was conducted in Mayangan coastal, Pamanukan, West Java from June-November 2003. The collected fish are 323 females and 195 males. The fish is carnivorous, euryphagic and bottom feeder. The primary food is crustacean and fishes, the additional is polychaetas, gastropods, pelecypods and sipunculidea. The food quality and quantity are relatively the same between the females and males. The inter class size niche breadth and the sexual food overlap shown the food competition between them happened. But based on the value of condition factor which is relatively stable. The food competition is little, because maybe the food resoueces is enough.